Enhancing stability and efficiency of perovskite solar cells with crosslinkable silane-functionalized and doped fullerene - Yang Bai (Nature Portfolio, 2016)
Perovskite solar cells reach high efficiencies but their stability remains a challenge. Here, Bai et al. functionalize the fullerene-based transport layer with hydrophobic and crosslinkable molecules to prepare devices reaching 19% efficiency and degrading by 10% over a month in ambient conditions.